2016
DOI: 10.1021/acsami.6b09504
|View full text |Cite
|
Sign up to set email alerts
|

Local Controllable Laser Patterning of Polymers Induced by Graphene Material

Abstract: Graphene has been successfully applied to the field of polymer laser patterning. As an efficient 1064 nm near-infrared (NIR) pulsed laser absorber, only 0.005 wt % (50 ppm) of graphene prepared by mechanical exfoliation endowed polymer materials with very good NIR pulsed laser patterning. Optical microscopy observed that the generated black patterns came from the local discoloration of the polymer surface subjected to the laser irradiation, and the depth of the discolored layer was determined to be within 221-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
3
36
1
Order By: Relevance
“…In this case, additives are required. These compounds can be either organic dyes (cyanine), metal complexes (copper complexes), or nano/microparticles (e.g., TiO 2 , Sb 2 O 3 , SnO 2 :Sb 2 O 3 , BiO 2 , black carbon, and graphene). Though the concentration of additives remains at a very low level (typically from 0.01 to 3.0 wt.…”
Section: Comparison Of Ink Aging After a Standard Uv Inkjet Processinmentioning
confidence: 99%
“…In this case, additives are required. These compounds can be either organic dyes (cyanine), metal complexes (copper complexes), or nano/microparticles (e.g., TiO 2 , Sb 2 O 3 , SnO 2 :Sb 2 O 3 , BiO 2 , black carbon, and graphene). Though the concentration of additives remains at a very low level (typically from 0.01 to 3.0 wt.…”
Section: Comparison Of Ink Aging After a Standard Uv Inkjet Processinmentioning
confidence: 99%
“…Zheng Cao et al [42] showed that 0.02% MoS 2 content and the selection of appropriate marking parameters result in obtaining graphic signs with high contrast. Wen et al [43] found that the addition of only 0.005 wt% graphene in the matrix of the material acts as an effective absorber of laser pulses in the near-infrared range. Zhou et al [44] proved that the use of carbon nanotubes affects the obtaining of high contrast between the graphic symbol and the background in the case of PP marking.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of a typical laser-irradiated material shows black marking by carbonization, 10 light/white marking by foaming, and color changes by the photothermal reaction. 11 In recent years, laser marking technology has been used in the fields of metals, 1214 ceramics, 15,16 plastics, 1719 and wet soft materials. 20,21 Compared with the conventional printing method, laser marking is a fast and flexible process technology and more environmentally friendly, and the contrast and durability are also improved.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-sensitive additives are capable of absorbing laser energy well and causing local overheating, leading to carbonization and formation of black markings. Laser marking sensitizers are mainly classified into inorganic, 18,19,23 organic, 24,25 and polymer/inorganic composite materials. 21,26,27 Wen et al 19 studied the use of graphene in the field of polymer laser patterning.…”
Section: Introductionmentioning
confidence: 99%